KARAKTERISTIK EMULSI MINYAK SAWIT MERAH DAN APLIKASI QUALITY FUNCTION DEPLOYMENT (QFD) UNTUK PENGEMBANGAN PRODUK - Sri Wulandari, Budiyanto dan Evanila Silvia (Department of Agroindustrial Technology, Bogor Agricultural University, 2015)
This research aimed to identify the characteristic of red palm olein emulsion, the importance of thequality attributes and technical process and to recommend development of red palm olein emulsion’s based onQuality Function Deployment applications. Identification of emulsion characteristic on color was analyzed withMunsell Colour Chart, viscosity with Viscometer Ostwald and emulsion stability based on period of time changeof emulsion characteristic. The results of this research found out that emulsion color is yellow (5Y 8????10),emulsion stability : ± 5 days and viscosity : 50,4 cP. The level of importance of quality attributes red palm oleinemulsion based on sixquality attributes, the emulsion stability is a priority in assessing the quality of red palmolein emulsion with the value 0.223 followed by color(0.180), taste (0.177), aroma (0.159), viscosity (0.136) andflavor (0.124). The importance level of technical process that are intimately associated with the quality attributesof red palm olein emulsionin the process of homogenitation II (0.454), process of adding complementarymaterials(0.432),and homogenitation I (0.114). The recommendations to improve of products on the attributesemulsion stability.Keywords: emulsion of red palm olein, QFD, emulsion stability, viscosity, color